PROTECTION OF THE WOLF IN THE CONTEXT OF POLISH ADMINISTRATIVE LAW - Sobieraj, Kamila; Zacharczuk, Piotr (Review of European and Comparative Law, 2020)
In view of the fact that about 80% of the wolf ’s population in Europe is of cross-border type, the conservation status of a particular wolf ’s population depends on the sum of the states national regulations sharing the population. The Polish national regulations thus have an impact upon the protection of three wolf ’s populations in Europe. They should thus become an object of interest also at the international forum. This article presents the broad-based Polish system of administrative and legal regulations of wolf ’s protection aimed at accomplishment of international and EU obligations. Poland, due to the relatively advanced level of legal protection of the wolf, may play a substantial role in restoring the population of this carnivore to the territories of many western European countries (the process already initiated through the presence of Polish wolves in Germany).